Comparison of 3 analytical techniques for the extraction and determination of 5 possible contaminants in food contact recycled materials. - Parigoridi, Ioanna-Efpraxia; Tsoumani, Eleftheria; Demertzis, Panagiotis G.; Akrida-Demertzi, Konstantoula (Technical Annals, 2023)
Climate change and ecological crises have become pressing matters to Europe and the world. In an attempt to put a halt to the massive production of packaging waste, the European Standardization Organisation (CENELEC) has developed harmonized standards to promote reuse, recycling, and other forms of recovering packaging waste. However, when implemented in the food and beverage industry, possible contaminants present in these recycled packaging materials could compromise public health. The present study is part of an ongoing research aiming to develop fast, simple, and reliable analytical methods to identify such contaminants in recycled materials intended to come in contact with foodstuffs. To this end, three extraction methods were developed and assessed regarding their effectiveness and accuracy in isolating a mixture of five possible contaminants [Benzophenone (BP), 2,6-Diisopropylnaphthalene (2,6-DiPN), 2,7-Diisopropylnaphthalene (2,7-DiPN), o-Terphenyl (o-TPH), and m-Terphenyl (m-TPH)] in samples of recycled paperboard materials: the Soxtec Extraction (SE), the Ultrasound-Assisted Extraction (UAE), and the Head Space Solid Phase Micro Extraction (HS-SPME. The HS-SPME analysis, with the use of Polydimethylsiloxane/ Divinylbenzene SPME fiber, yielded the best analytical results compared to the other two. Accordingly, the analysis of variance (ANOVA) and multivariate analysis of variance (MANOVA) further supported these results.